Post-transplant cyclophosphamide alters immune signatures and leads to impaired T cell reconstitution in allogeneic hematopoietic stem cell transplant - Chenchen Zhao; Matthew Bartock; Bei Jia; Neal Shah; David F. Claxton; Baldeep Wirk; Kevin L. Rakszawski; Myles S. Nickolich; Seema G. Naik; Witold B. Rybka; W Christopher C. Ehmann; Raymond J. Hohl; et al. (Journal of Hematology & Oncology, 2022)
Abstract Despite the increased usage of post-transplant cyclophosphamide (PTCy) in allogeneic hematopoietic stem cell transplantation (allo-HSCT), our knowledge of immune reconstitution post-allo-HSCT in the setting of PTCy is limited. Adequate immune reconstitution is the key to a successful transplant. In this study, we aim to investigate the effect of PTCy on the reconstitution of each immune component; more focus was placed on the immunophenotype and functions of T cells. Using blood samples from patients who underwent allo-HSCT under regimens containing PTCy (n = 23) versus those who received no PTCy (n = 14), we examined the impact of PTCy on the post-transplant immune response. We demonstrated a distinct T cell immune signature between PTCy versus non-PTCy group. PTCy significantly delayed T cell reconstitution and affected the T cell subsets by increasing regulatory T cells (Treg) while reducing naïve T cells. In addition, we observed remarkable enhancement of multiple inhibitory receptors (TIGIT, PD-1, TIM-3, CD38, CD39) on both CD4+ and CD8+ T cells on day 30 post-transplantation in patients who received PTCy. Importantly, upregulation of PD-1 on CD8 T cells was persistent through day 180 and these T cells were less functional, manifested by reduced cytokine production upon anti-CD3/CD28 stimulation. Furthermore, we found a significant correlation of T cell immune phenotypes to clinical outcome (disease relapse and GVHD) in patients who received PTCy. Our novel findings provide critical information to understand the mechanism of how PTCy impacts immune reconstitution in allo-HSCT and may subsequently lead to optimization of our clinical practice using this treatment.